Response of nutrient management on growth, yield and nutrient uptake of hybrid rice in Gangetic plains of West Bengal - Mondal, Chiranjiv; Sana, Megha; Mondal, Ramyajit; Mandal, Sudip; Banerjee, Hirak; Pal, Sukanta (ORYZA-An International Journal of Rice, 2022)
A field experiment was conducted at Regional Research Sub-Station (RRS), under Bidhan Chandra Krishi Viswavidyalaya, Chakdaha, Nadia, West Bengal during rainy seasons of 2017 and 2018 to study the effect of different nutrient management on growth, yield and nutrient uptake of hybrid rice. The experiment was laid out in factorial randomized block design with 20 treatment combinations having 4 varieties (3 hybrid varieties and 1 high yielding variety) and 5 combinations of nutrient management in three replications. The treatment combination of Ajay variety with 50% recommended dose of nitrogen (RDN) + 50% RDN from mustard cake + full recommended dose of phosphorus (RDP) and potassium (RDK) recorded the highest plant height but significantly greater values of leaf area index at 75 days after transplanting (DAT), leaf area duration at 30-90 DAT, dry matter accumulation and crop growth rate at 60-75 DAT were recorded in the treatment combination of Arize 6444 with 75% RDN + 25% nitrogen through mustard cake + 20 kg ZnSO4 /ha. In terms of yield attributes and yield treatment combination of hybrid variety Arize 6444 when combined with either of the fertilizer treatment i.e., 50% RDN + 50% RDN from mustard cake + full (RDP) and (RDK) or 75% RDN + 25% RDN from mustard cake + RDP and RDK + 20 kg ZnSO4 ha-1 recorded significantly (p= 0.05) best results. Hence, this combination could be more effective in augmenting growth, yield and nutrient uptake in the Gangetic plains of West Bengal.